Estudio de variaciones en los términos de comercio internacional (Incoterms®) (2020)
A study of the changes presented to the Incoterms® in the updates was carried out, in order to know why these adjustments were made and what they were, for this reason, a historical account was made of the Incoterms® and an analysis of international trade in the last decade.